GOVERNMENT INTERFERENCE IN TRADITIONAL LEADERSHIP AND COMMUNITY DEVELOPMENT IN AKWA IBOM STATE, NIGERIA - Mbon, Namso (AKSU Annals of Sustainable Development, 2025)
Before now traditional leaderships were bound by normative principles to rule with consent of the people in compliance with norms of their respective communities. Appeal to enthronement of traditional leaders were based on the virtues of the ancestral background of the person who would be chosen or appointed as community leader in accordance with the prescription of the rituals of the community deity. But fairly recently, traditional leadership has become elevated stool either by struggle or appointment by political player. Therefore, the study examines the effect of government interference on traditional leadership and community development in Akwa Ibom State. The study adopted survey research method alongside cluster and stratified sampling techniques to gather data from the three major ethnic group in the state. Hypotheses were tested and analyzed using simple regression statistical tool. Findings reveals that, issuance of certificate of recognition to traditional leaders by governments impedes substance of culture and norms in communities. Also payments of remuneration to traditional leaders create leadership tussle in communities. The study recommended that government should make laws to prohibited issuance of certificate of recognition to traditional leaders and revert to supporting ancestral principles for selection of traditional leaders in order to sustain cultural heritage and foster community development in the state. Also, payment of remuneration to traditional leaders should be abolish and stop to forestall leadership tussle and permeate sustainability of culture to foment community development in the state.